Impacts of Animal Health Interventions on Women's Empowerment in Extensive Livestock Systems of Ethiopia: A Narrative Review - Gehano, Gelano; Shiferaw, Dessie; Radeny, Maren A.O.; Gondwe, Therese; Mekuriaw, Shigdaf; Van Dijk, Suzanne (International Livestock Research Institute, 2025)
In low- and middle-income nations, healthy livestock offers significant opportunities for women's empowerment. In Ethiopia, the widespread prevalence of many infectious and parasitic diseases drastically constrains the production and productivity of livestock through morbidity, mortality and market restrictions. Women livestock keepers tend to own more small ruminants (goats and sheep) and poultry, and their livelihoods are adversely affected if their herds are not protected against these diseases. Livestock farming has gender-specific challenges and opportunities, with implications for empowering women smallholder farmers and their household well-being, food security, and livelihoods. Gender-based limitations constrain women's access to animal health services, which has a detrimental impact on their livestock reproduction and productivity. There is a need to measure how women benefit personally, socially, and economically from strategic animal health interventions. Yet, very few studies in other countries measure whether interventions empower women and smallholder livestock farmers. Thus, this review aimed to collect and synthesize available information on the impacts of strategic animal health interventions on women's empowerment from Ethiopia and elsewhere in extensive livestock production systems by a narrative review approach. Evidence demonstrated the presence of a strong positive relationship between women's empowerment and the use of animal health interventions. Likewise, the empowerment of women contributed to the greater adoption of interventions. Nevertheless, a dearth of concrete information was available in Ethiopia on the impacts of animal health interventions on women’s empowerment. Women were disproportionately affected by zoonotic and infectious diseases compared to men due to their intimate relationship with livestock and raw animal products, and dependency on livestock. Various studies reported the impacts of animal health interventions on livestock health and production parameters, not women’s empowerment. Thus, more research is needed to assess the effects of previous and ongoing animal health interventions on women’s empowerment, particularly in livestock-dependent rural communities.